Organocatalyzed Ring‐Opening Polymerization of (S)‐3‐Benzylmorpholine‐2, 5‐Dione. Issue 3 (11th December 2022) - Göppert, Natalie E.; Dirauf, Michael; Liebing, Phil; Weber, Christine; Schubert, Ulrich S.
Abstract: A 3‐benzylmorpholine‐2, 5‐dione monomer is synthesized from the natural amino acid l ‐phenylalanine and characterized by means of nuclear magnetic resonance and infrared spectroscopy, electrospray ionization mass spectrometry, and elemental analysis. Subsequent to preliminary polymerization studies, a well‐defined poly(ester amide) homopolymer is synthesized via ring‐opening polymerization using a binary catalyst system comprising 1, 8‐diazabicyclo[5.4.0]undec‐7‐ene (DBU) and a 1‐(3, 5‐bis(trifluoromethyl)phenyl)‐3‐cyclohexylthiourea (TU) cocatalyst with a feed ratio of M/I/DBU/TU = 100/1/1/10. Kinetic studies reveal high controllability of the dispersities and molar masses up to conversions of almost 80%. Analysis by mass spectrometry hints toward excellent end‐group fidelity at these conditions. In consequence, utilization of hydroxyl‐functionalized poly(ethylene glycol) and poly(2‐ethyl‐2‐oxazoline) as macroinitiators results in amphiphilic block copolymers. Bulk miscibility of the building blocks is indicated by differential scanning calorimetry investigations. As more and more promising new drugs are based on hydrophobic molecules featuring aromatic moieties, the novel polyesteramides seem highly promising materials to be used as potential drug delivery vehicles. Abstract : A 3‐benzylmorpholine‐2, 5‐dione monomer is synthesized from the natural amino acid l ‐phenylalanine and polymerized via ring‐opening polymerization using a binary catalyst system comprising 1, 8‐diazabicyclo[5.4.0]undec‐7‐ene (DBU) and a thiourea cocatalyst resulting in a well‐defined poly(ester amide) homopolymer. Amphiphilic block copolymers are obtained by utilizing hydroxyl‐functionalized poly(ethylene glycol) and poly(2‐ethyl‐2‐oxazoline) as macroinitiators.